A new approach to the prevention and treatment of delirium in elderly patients in the intensive care unit - Andrew B. Rosenzweig; Charmian D. Sittambalam (Greater Baltimore Medical Center, 2015)
The pronounced prevalence of delirium in geriatric patients admitted to the intensive care unit (ICU) and its increased morbidity and mortality is a well-established phenomenon. The purpose of this review is to explore the potential use of dexmedetomidine in preventing or managing ICU delirium in older patients. Articles used were identified and selected through multiple search engines, including Google Scholar, PubMed, and MEDLINE. Keywords such as dexmedetomidine, delirium, geriatric, ICU delirium, delirium in elderly, and palliative were used to obtain the specific articles used for this paper and restricted to articles published in 1990 or later. Articles specifically looking at the use of dexmedetomidine as compared to a study drug and its potential for use in ICU patients, as opposed to overall reviews of dexmedetomidine, were compared. When compared to benzodiazepines for the prevention or treatment of ICU delirium in the elderly, dexmedetomidine was associated with a reduction in delirium, as well as decreased morbidity and mortality. Dexmedetomidine has also been shown to be effective in limiting risk factors associated with ICU delirium such as length and depth of sedation. As opposed to benzodiazepines or opiates, dexmedetomidine provides effective analgesia, sympatholysis, and anxiolysis without causing respiratory depression and allows a patient to more effectively interact with practitioners. The review of these nine articles indicates that these favorable attributes and overall decreased duration and incidence of delirium make dexmedetomidine a viable option in preventing or reducing ICU delirium in high-risk geriatric patients and as a palliative adjunct to help control symptoms and stressors.